Study on p-Wave Attenuation in Hydrate-Bearing Sediments Based on BISQ Model. (9th October 2013) - Li, Chuanhui; Feng, Kai; Liu, Xuewei
Abstract : In hydrate-bearing sediments, the elastic wave attenuation characteristics depend on the elastic properties of the sediments themselves on the one hand, and on the other hand, they also depend on the hydrate occurrence state and hydrate saturation. Since the hydrate-bearing sediments always have high porosity, so they show significant porous medium characteristics. Based on the BISQ porous medium model which is the most widely used model to study the attenuation characteristics in the porous media, we focused on p-wave attenuation in hydrate-bearing sediments in Shenhu Area, South China Sea, especially in specific seismic frequency range, which lays a foundation for the identification of gas hydrates by using seismic wave attenuation in Shenhu Area, South China Sea. Our results depict that seismic wave attenuation is an effective attribute to identify gas hydrates.